Analisis Efisiensi KB Bank Syariah Periode 2018-2023 Menggunakan Pendekatan DEA - Adinda Meyta Saharani; Ninda Ardiani (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The purpose of this study is to analyze / examine and compare how the level of efficiency generated by PT. Bank KB Bukopin in 2018-2020 (the phase before the transfer of the bank's main share ownership) with 2021-2023 (the phase after the transfer of the bank's main shares), so unlike many previous studies, this study will use only 1 type of bank, namely KB Bank Syariah. In this study, the data used is secondary data in the form of financial reports obtained from the official website / official website of KB Bank Syariah. The data analysis method used to analyze efficiency at KB Bank Syariah before and after the transfer of the bank's main share ownership is Data Envelopment Analysis (DEA) with an intermediation approach with VRS assumptions. The results of this study conclude that the efficiency generated by KB Bank Syariah in the 2018-2023 period experienced fluctuations where the period before the transfer of the main shares can be said to be more efficient than the period after the transfer of the main shares of KB Bank Syariah. The causes of inefficiency include total assets, income, labor costs and financing.